Assistance In Strengthening Qur’an Recitation Through The Talaqqi Method To Improve The Quality Of Reading In TPQ At Sumberkerep Village - Pristiwiyanto; Atmari; Kholishudin; Sandi, Misella; Krismawati, Ana Daulika (PUDAK: Local Wisdom Community Journal, 2025)
Reciting the Qur'an with proper tahsin and in accordance with the correct makharijul huruf is a fardhu kifayah obligation for Muslims. This skill is essential to ensure that Qur'anic recitation adheres to the established rules of tajweed. However, at TPQ Desa Sumber Kerep, Kecamatan Mantup, Kabupaten Lamongan, several fundamental issues have been identified regarding the ability of teachers and students to articulate the letters of the Qur'an correctly. Common errors include mispronunciation of letters that do not align with their proper makhraj (place of articulation), thus affecting the accuracy of Qur'anic recitation. The Asset-Based Community Development (ABCD) approach offers an alternative method for empowering communities by utilizing the assets possessed by the community. In this context, assets refer to the potential or strengths within the community, including individual capabilities (such as intelligence, empathy, and collaboration) as well as available natural resources. By optimizing these potentials, empowerment programs can be designed to enhance Qur'anic recitation skills. The implementation of ABCD-based programs has proven effective in improving the quality of Qur'anic recitation for both teachers and students at TPQ Desa Sumber Kerep. This program provides a strong foundation for sustainable Qur'anic learning. To ensure continuity and further improvement in the proficiency of makharijul huruf, it is recommended to conduct regular training sessions accompanied by periodic evaluations to achieve optimal results.